Nutrient content and uptake of field pea and baby corn intercrops as affected by weed management and planting patterns - Devi, Moirangthem Thoithoi; Singh, V.K. (Annals of Agricultural Research, 2016)
A field experiment was conducted during two consecutive seasons of rabi 2011-13 at G.B. Pant University of Agriculture Technology, Pantnagar to find out the effect of planting pattern and weed management practices on yields, and nutrient content and uptake of field pea and baby corn in field pea (Pant P-13) + baby corn (Surya) intercropping system. The experiment was laid-out in split-plot design keeping four planting patterns as main-plot and four weed management practices as sub plot with three replications. Sole planting of field pea recorded significantly higher grain (2264 and 1434 kg ha-1) and straw yields (3263 and 2540 kg ha-1) during 2011-12 and 2012-2013 than yield obtained as a component crop in paired planting of maize (30/60 cm) + field pea (2:2) and planting of maize + field pea (1:1). Baby corn yield was similar in sole, paired (2:2) and 1:1 planting, but significantly higher stover yield of baby corn (3576 kg ha-1and 3533 kg ha-1, during 2011-12 and 2012-2013, respectively) was obtained from sole crop than other planting methods during both years. Sole planting of either field pea or baby corn recorded significantly higher total nitrogen, phosphorus and potassium uptake than planting of maize + field pea (1:1) and paired planting of maize (30/60 cm) + field pea (2:2) during both the years. Hand weeding (HW) at 30 days after sowing (DAS), pre emergence application of pendimethalin 1 kg ha-1 and post emergence application of imazethapyr 50 g ha-1 (30 DAS) improved yields of field pea and baby corn than weedy check. Hand weeding (30 DAS) and pre-emergence application of pendimethalin 1 kg ha-1 resulted in higher total nitrogen, phosphorus and potassium uptake by field pea and baby corn as compared to post emergence application of imazethapyr 50 g ha-1(30 DAS) and